Higher Right Hemisphere Gamma Band Lateralization and Suggestion of a Sensitive Period for Vocal Auditory Emotional Stimuli Recognition in Unilateral Cochlear Implant Children: An EEG Study - Cartocci, Giulia; Giorgi, Andrea; Inguscio, Bianca M. S.; Scorpecci, Alessandro; Giannantonio, Sara; De Lucia, Antonietta; Garofalo, Sabina; Grassia, Rosa; Leone, Carlo Antonio; Longo, Patrizia; Freni, Francesco; Malerba, Paolo; et al. (Frontiers in Neuroscience, 2021)
In deaf children huge emphasis was given to language, however emotional cues decoding and production appears of pivotal importance for communication capabilities. Concerning neurophysiological correlates of emotional processing, the gamma band activity appears a useful tool adopted for emotion classification and related to the conscious elaboration of emotions. Starting from these considerations the following items have been investigated: i) Whether emotional auditory stimuli processing differs between normal hearing children (NH) and children using a cochlear implant (CI), given the non-physiological development of the auditory system in the latter group ii) Whether the age at CI surgery influences emotion recognition capabilities iii) In the light of the right hemisphere hypothesis for emotional processing, whether the CI side influences the processing of emotional cues in unilateral CI (UCI) children. To answer these matters 9 UCI (9.47±2.33 years old) and 10 NH (10.95±2.11 years old) children were asked to recognize non-verbal vocalizations belonging to three emotional states: positive (achievement, amusement, contentment, relief), negative (anger, disgust, fear, sadness) and neutral (neutral, surprise). Results showed better performances in NH than UCI children in emotional states recognition. The UCI group showed increased gamma activity lateralization index (LI) (relative higher right hemisphere activity) in comparison to the NH group in response to emotional auditory cues. Moreover, LI gamma values were negatively correlated with the percentage of correct responses in emotion recognition. Such observations could be explained by a deficit in UCI children in engaging the left hemisphere for more demanding emotional task, or alternatively by a higher conscious elaboration in UCI than NH children. Additionally, for the UCI group there was no difference between the CI side and the contralateral side in gamma activity, but it was found a higher gamma activity in the right in comparison to the left hemisphere. Therefore, the CI side did not appear to influence the physiologic hemispheric lateralization of emotional processing. Finally, it was showed a negative correlation between the age at the CI surgery and the percentage of correct responses in emotion recognition, then suggesting the occurrence of a sensitive period for CI surgery for best emotion recognition skills development.